The role of socialisation of the forest management system in Poland in the face of the need to mitigate climate change - Karaczun Zbigniew M.; Bojanowski Jakub (Environmental Protection and Natural Resources, 2022)
Climate change will have a significant impact on forests as most of the factors determining their condition are modified by the effects of the climate change process. Some of these effects are a change in the distribution and amount of precipitation, an increase in the frequency of extreme meteorological phenomena, including hurricane winds, temperature distribution, or a change in the length of the growing season. In order to maintain the productivity of Polish forests and the range of ecosystem services they provide, the forestry sector will have to adapt to these changes. However, forestry will also have to take a part in holding back climate change. Achieving climate neutrality by mid-21st century and ensuring a 55% reduction in greenhouse gas emissions by 2030 will not be possible without using the ability of forests to absorb and permanently store carbon.